2013
DOI: 10.1186/1472-6823-13-25
|View full text |Cite
|
Sign up to set email alerts
|

What’s distressing about having type 1 diabetes? A qualitative study of young adults’ perspectives

Abstract: BackgroundDiabetes distress is a general term that refers to the emotional burdens, anxieties, frustrations, stressors and worries that stem from managing a severe, complex condition like Type 1 diabetes. To date there has been limited research on diabetes-related distress in younger people with Type 1 diabetes. This qualitative study aimed to identify causes of diabetes distress in a sample of young adults with Type 1 diabetes.MethodsSemi-structured interviews with 35 individuals with Type 1 diabetes (23–30 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
156
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(189 citation statements)
references
References 47 publications
(75 reference statements)
21
156
0
5
Order By: Relevance
“…Indeed, the most commonly reported emotional problems in Type 1 diabetes relate to hypoglycaemia and complications; worry about the future and complications, feeling burnt out/overwhelmed, and worrying about low blood sugar reactions (5-7), whereas in Type 2 diabetes emotional distress relates more to goal setting and food restrictions (7). Qualitative work confirms stressors unique to Type 1 diabetes; realisation of the possible consequences of previously poor self-management as adolescents, apprehension about pregnancy, anxiety about being perceived to have Type 2 diabetes, frustration competing for resources with Type 2 diabetes and a great many concerns specific to insulin use (8,9). Our own case note documentary analysis observed differences in the manifestation of DD in the two populations (10).…”
Section: Manifestation Of Diabetes Distress In Type 1 and Type 2 Diabmentioning
confidence: 62%
“…Indeed, the most commonly reported emotional problems in Type 1 diabetes relate to hypoglycaemia and complications; worry about the future and complications, feeling burnt out/overwhelmed, and worrying about low blood sugar reactions (5-7), whereas in Type 2 diabetes emotional distress relates more to goal setting and food restrictions (7). Qualitative work confirms stressors unique to Type 1 diabetes; realisation of the possible consequences of previously poor self-management as adolescents, apprehension about pregnancy, anxiety about being perceived to have Type 2 diabetes, frustration competing for resources with Type 2 diabetes and a great many concerns specific to insulin use (8,9). Our own case note documentary analysis observed differences in the manifestation of DD in the two populations (10).…”
Section: Manifestation Of Diabetes Distress In Type 1 and Type 2 Diabmentioning
confidence: 62%
“…This finding is somewhat unsurprising given distinctions in the developer's goals, and some of the relative omissions may reflect imbalance in the populations from which the items were derived in accordance with these aims. For example, numerous aspects of DD that are unique to type 1 diabetes have recently been identified (Balfe et al, 2013;Fisher et al, 2015) and this formed the basis for developing the T1-DDS (Fisher et al, 2015). They may also reflect distinctions in methodological approach; the DDS items reflect four domains considered central to diabetes-related emotional distress created a priori based on focus groups discussions whereas the PAID was not apparently informed by any such structure when it was developed 10 years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Explicit description of development work is critical so that readers are able to discern whether content validity has been achieved (European Medicines Agency Committee for Medicinal Products for Human Use, 2005; U.S. Department of Health and Human Services, 2009). In the absence of further information, and recent qualitative research suggesting aspects of DD that are not captured in these measures (Balfe et al, 2013;Tanenbaum et al, 2016), it does not appear that any single existing measure of DD meets required standards for assuring content validity or offers a fully comprehensive measure of DD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychological impacts of diabetes resulting in depression, anxiety, and distress can negatively affect self-management and quality of life, especially for young people [4]. Balfe and colleagues found that young adults with type 1 diabetes experienced distress regarding their daily management needs, stigma, and worry about their future [5]. In a study by Palladino et al [6], emerging adults with diabetes report lower level of life satisfaction and life purpose than peers living without type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%